Propagação agâmica das palmas gigante - Opuntia ficus-indica (L.) Mill. e doce - Nopalea cochenillifera (L.) Salm.-Dick Asexual propagation of giant and sweet cacti - Opuntia ficus-indica (L.) Mill. and Nopalea cochenillifera (L.) Salm.-Dick (Revista Ciência Agronômica, 2023)
RCA